Analisis Sensitivitas Dalam Metode Analytic Hierarchy Process dan Pengaruhnya Terhadap Urutan Prioritas Pada Pemilihan Smartphone Android - Yakoba Yusina Muanley; Aloisius Loka Son; Grandianus Seda Mada; Nugraha K. F. Dethan (VARIANSI: Journal of Statistics and Its application on Teaching and Research, 2022)
Smartphones nowadays have become a basic need for everyone because they provide many benefits and conveniences for users. People always want to have a smartphone with good quality. However, due to the lack of information along with the many types of smartphones in circulation, it often makes it difficult for users to choose a smartphone that suits their needs. To overcome these problems, it is necessary to have a method that can provide recommendations for appropriate decision-making for users. This study aims to apply the Analytic Hierarchy Process (AHP) method and sensitivity analysis in determining the priority order of smartphone selection by comparing one smartphone to another. The criteria for consideration are Facilities, Price, Battery, and RAM with alternative choices in the form of Xiaomi, Oppo, and Vivo brand smartphones. Data collection in this study was carried out by distributing questionnaires to 100 students of the Mathematics Study Program. The data were processed using the AHP method and sensitivity analysis. AHP is used to produce a more consistent ranking order of each alternative, while the sensitivity test is carried out to measure the stability of the calculation results if there is a change in decision-making. From the results of the analysis with AHP, it was found that Xiaomi was the first priority of the respondent's choice, followed by Vivo, and the last priority was Oppo with an inconsistency level of 0.02. Meanwhile, sensitivity testing shows that RAM is the most influential criterion for changing the order of alternative priorities, where Xiaomi remains the first priority, followed by Oppo, and Vivo is the last priority.